G. V. F. Hegel: in searching for an authentic image (to the 250th anniversary of birth) - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The anniversary, celebrated in 2020 in honor of the 250th anniversary of G. Hegelʼs birth and the 200th anniversary of the publication of his «Philosophy of Right», gives us a good reason to intensify work on further study of his inheritance. The article attempts to briefly describe the many images of G. Hegel and his philosophy, that have developed in philosophical literature over the past 200 years. Starting with his closest supporters and opponents – the «Old» and «Young» Hegelians; then the founders of Marxism, V. Lenin, the French Neohegelians in the person of A. Kozhev and J. Val; the subsequent tough confrontation between the images of G. Hegel formed by K. Popper and H. Markuse, and ending with the research of J. DʼOnt and the concept developed by the organisers of the 33rd International Hegel Congress (June 2021), the essence of which is the need to correct the ideologically insulted image of G. Hegel and positioning him as a thinker of freedom. It is noted that in the 21st century we cannot remain captive of odious ideological cliches and stereotypes, that impose on us the image of a thinker as an apologist of the Prussian State and a conservative reactionary, designed to keep philosophy within reasonable boundaries, as well as impose on him responsibility for what was said on his behalf by supporters of either orthodox Marxism or radical neohegelians.
Keywords: G. Hegel; «clash of different faces of Hegel»; K. Marx; V. Lenin; neohelianism; A. Kozhev; K. Popper; H. Markuse; V. Stеpin; J. DʼOnt; 33rd Intertanional Hegel congress